2016
DOI: 10.1038/srep32169
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lionfish reduce native fish abundance on a regional scale

Abstract: Invasive lionfish pose an unprecedented threat to biodiversity and fisheries throughout Atlantic waters off of the southeastern United States, the Caribbean, and the Gulf of Mexico. Here, we employ a spatially replicated Before-After-Control-Impact analysis with temporal pairing to quantify for the first time the impact of the lionfish invasion on native fish abundance across a broad regional scale and over the entire duration of the lionfish invasion (1990–2014). Our results suggest that 1) lionfish-impacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 31 publications
(52 reference statements)
0
47
0
3
Order By: Relevance
“…The losses observed so far have affected prey‐sized fishes (usually <10 cm L T ), as Albins & Hixon () had speculated, but even within longer studies, these losses have not translated into similar deficits in larger prey size classes (Green et al, ; Albins, ). The one possible exception is the regional decline of adult tomtate grunt Haemulon aurolineatum Cuvier 1830 off the south‐eastern U.S.A. (Table ), which has been attributed to lionfish predation on juveniles (Ballew et al, ). It might ultimately be difficult to ascribe part or all of downward trends in commercially important species to lionfish predation because of the coarseness of most fisheries data and the multiple stressors (including fishing) affecting these species.…”
Section: Has the Worst‐case Scenario Come To Pass?mentioning
confidence: 99%
See 2 more Smart Citations
“…The losses observed so far have affected prey‐sized fishes (usually <10 cm L T ), as Albins & Hixon () had speculated, but even within longer studies, these losses have not translated into similar deficits in larger prey size classes (Green et al, ; Albins, ). The one possible exception is the regional decline of adult tomtate grunt Haemulon aurolineatum Cuvier 1830 off the south‐eastern U.S.A. (Table ), which has been attributed to lionfish predation on juveniles (Ballew et al, ). It might ultimately be difficult to ascribe part or all of downward trends in commercially important species to lionfish predation because of the coarseness of most fisheries data and the multiple stressors (including fishing) affecting these species.…”
Section: Has the Worst‐case Scenario Come To Pass?mentioning
confidence: 99%
“…Ballew et al . () found no changes in predatory fish numbers while lionfish density increased and H. aurolineatum abundance tumbled on the south‐east coast of the U.S.A. On one Bahamian mesophotic reef, however, there appears to have been a wholesale replacement of native mesopredators by the same density of lionfish (Lesser & Slattery, ), although the mechanism by which this substitution occurred is unclear. Other declines of mesopredators occurring concurrently with a build‐up of lionfish numbers cannot be clearly ascribed to predation or competition (Green et al, ; Tuttle, ).…”
Section: Has the Worst‐case Scenario Come To Pass?mentioning
confidence: 99%
See 1 more Smart Citation
“…Released by accident or misadventure in the mid-1980s off the coast of Florida, they have spread throughout the Caribbean, where populations have grown exponentially, with substantial impact to the community composition (Betancur-R et al ., 2011; Albins and Hixon, 2013; Côté et al ., 2013; Benkwitt, 2014; Ballew et al ., 2016). Densities in some places of the Caribbean have been estimated at 400 ha −1 (Morris and Whitfield, 2009), with lionfish consuming 8–10% of their body weight per day (Green et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…triseriatus larval abundance. Alterations to host density is one of the purported mechanisms of the dilution effect (Keesing et al, ), and one of the negative impacts invasive species has been shown to have on some native species (Ballew, Bacheler, Kellison, & Schueller, ). Previous laboratory studies have shown little asymmetrical competition between the two mosquito species in our study (Freed, Kesavaraju, & Leisnham, ; Hardstone & Andreadis, ), although we did predict that the removal of Ae .…”
Section: Discussionmentioning
confidence: 99%